“Vocês vão começar a dar aulas remotas agora. Pronto! E daí? O que você faz?”: vivências de professores de língua inglesa antes, durante e depois do cronotopo pandêmico - Sgorla, Kristian (2025)
This research analyzes the professional and personal experiences of English teachers in private middle schools in Foz do Iguaçu/PR in three different chronotopes: before the Covid-19 pandemic, during the adoption of emergency remote teaching and hybrid teaching, and after the return to face-to-face classes. The aim is to reveal and compare the experiences of these professionals in the three periods mentioned, as well as the possible repercussions of the ERT and the HT on their professional and personal routines, considering that the concrete conditions to which they were exposed could have an effect on teaching. Portraying these experiences represents an unprecedented research effort, which discloses remote and hybrid pedagogical practices used by these teachers and highlights problems faced by them in carrying out their duties as teachers and citizens in a context of global health emergency. This contributes to a broader understanding of teaching and being a teacher during the pandemic, and how this may have impacted the post-pandemic elementary school English teacher. Thus, the general aim of this research is to expose and reflect on the professional and personal experiences of middle school English teachers in private schools in Foz do Iguaçu before Covid-19, during the adoption of ERT and HT motivated by the suspension of face-to-face classes due to the pandemic, and after the return to face-to-face teaching. In order to achieve this objective, the study is based on the transdisciplinary vision of research in Applied Linguistics (AL) (Kleiman, 1998; Celani, 2016), and is classified as a descriptive case study (Gil, 2002), which proposes a qualitative (Godoy, 1995) and interpretivist (Moita Lopes, 1994) analysis of data generated through semi-structured interviews (Boni; Quaresma, 2005) with three middle school English teachers from the private school system in the municipality, who worked before, during and after the suspension of face-to-face classes. The research analysis is based on the Bakhtinian philosophical perspective of language, specifically its conceptions of language, utterance (verbal and non-verbal), dialogism, heteroglossia and chronotope (Bakhtin, 2002, 2015, 2017, 2018). The study is also based on concepts of work analysis such as the Activity Clinic and its understanding of the dimensions of work (Clot, 2010a, 2011); on the main characteristics of the approaches and methods of English teaching used over time (Leffa, 1988, 2012; Kumaravadivelu, 2001); the digital possibilities indicated by the information technology paradigm (Castells, 2002) for teaching and learning processes; and the conceptualization of ERT (Bacich; Tanzi Neto; Trevisani, 2015; Moran, 2015) and HT (Arruda, 2020; Joye et al. 2020). Through this investigation, it was found that the ERT adopted by the schools in no way resembled the original proposal of DE; what has come to be called HT in the pandemic chronotope (Rohling, 2020) goes against the original proposal of HT; the digital literacy acquired by teachers during ERT and HT 11 allowed them to be inserted into the digital culture; the return to the face-to-face modality meant a resumption of the use of traditional pre-pandemic approaches and methods of English teaching; the adoption of ERT and HT increased the teachers' workload, reducing the time dedicated to their families, personal relationships, leisure and physical activities; and the teachers' reports associate their pandemic and post- pandemic pedagogical experiences to the development of mental illnesses such as stress and anxiety.